E –Waste Management in India; Treatment and Opportunities - Rahman, Rukia; Nisar, Shezaan; Dar, Bilal Ahmad; Ganaie, Aadil Ahmad; Tariq, Muhammad (Recent Research Reviews Journal, 2023)
The historical Industrial Revolution in the 18th century, which brought in a brand-new age for the enormous human race, was the cause of many advances in science and technology. In this 21st century people manage a lot of information’s via media and technology as well as personal lives, economies and industries. This in turn has only developed and the different allied systems in people’s lives which happen to have the relevance to the large-scale global advancement of the same. However, as is the case with most human inventions, there entails a grey side to this development also which has become to be holistically referred to as e-waste. E-waste (Electronic Waste)is anything electronic and electrical being disposed of, which by every metric poses a potential threat to the same fabric of life i.e., encompassing all forms of lives whether humans, animals, plants, etc. Consequently, the management of e-waste becomes highly imperative to a sustainable healthy living environment. The study bespeaks the condition of electronic trash in India, as well as potential, problems, and methods for managing it. This descriptive article also highlights the harmful health impacts, and the regulatory policies designed to safeguard marginalized citizens from improper e-waste disposal practices.